TEACHING QUESTION WORDS FOR ADULT LEANERS BY USING THE PICTURES OF SOMEBODY POPULAR AS A TEACHING MEDIA - Ali Amran (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
This study investigates and predicts the learners difficulties in using those question word : what, when, where, why, who, whose, whose, whose, which and how through out the pictures ol‘ somebody. Most new beginners of English language hope to speak the language they learn as soon as they can, without considering over about the langauge grammar, particularly in applying those question words."teachers can, of course, conduct many distinguish teaching medias or tools in order to improve the learners progress in learning a langauge. Mistakes notmanlly takes place when beginners learn, especially a new a language let alone when they try to speak, the slip 01° the tounge commonly happens. Beginners sometimes misused questions words, since they have some diftlerences and similarities in theirLl and in L2, especially What, Where, When due to having misleading about Question Words. The researcher found out that by using the pictures oi’ somebody, as a teaching media. The researcher strongly believes that the picture of somebody can minimize the mistakes and improve their speaking skills in terms of using question Words. Question words are used to ask about specilic qualities, times, places, people, etc. For example, when we look at the picture of somebody on TV, in Newspapers, and at some other certain places, then we suddenly can ask about the picture of that person.